Impact of Cooperative Learning in Developing Students' Cognitive Abilities for Academic Achievement - Bareerah Hafeez Hoorani (Journal of Education and Educational Development, 2014)
This study used an Action Research Method to investigate ways to improve the thinking and reasoning skills of grade eight science students in an under-resourced school in Karachi. The students’ rote learning patterns were challenged using the schema provided by Blooms’ taxonomy of learning domains. A cooperative learning environment was generated with a renewed investment plan, a restructured lesson plan and an intensive workshop with the group leaders. These interventions were done with the help of the preliminary data that was collected through questionnaires. The outcomes of the action research method showed a positive correlation between cooperative learning approach and academic achievement of the students.